STUDENT EXPERIENCES DURING THE ARGENTINE "AZOS" IN LATIN AMERICAN PERSPECTIVE - CALIFA, JUAN SEBASTIÁN (Universidad Nacional del Litoral, 2019)
In this interpretation essay were flect on the student experiences in the Argentine “azos” of the late sixties and early seventies of the twentieth century back lit with other student mobilizations in the region. Our attention will be given to the strategies that the students established, highlighting the alliances they drew. For this we consult the specific literature as well as the results that have begun to show our research.